Double-slit, Comprehensive-Double-Slit and Irregular-Double-Slit Experiments Showing That Light is Photons and It is Photons That Produce both Non-Interference Patterns and Interference Patterns in Same Experiment : PhotoWave Phenomena and Optics-Butterfly-Effect - Peng, Hui (European Journal of Applied Sciences, 2025)
Young’s double slit experiments have been descripted by wave theories, i.e., before and after passing through a double slit, the light is waves. To test the wave description, we extend the double slit experiments to the comprehensive double slit experiments which are the regular double slit experiments with added either Shield, or Blocker, or Metal tube, or Photon-Chamber, or Lens. The comprehensive double slit experiments show the novel phenomena: (1) the light is particles, not waves, before and after passing through a double slit; (2) it is the particles that form both the non-interference patterns (near the double slit) and interference patterns (near/on the detector) in the same experiment; (3) the non-interference patterns gradually evolve to the interference patterns in the same experiment. We refer to the novel phenomena as “PhotoWave phenomena” which are universal. For studying the wave theory further, we show the Irregular-Double-Slit Experiments including the non-parallel-double slit, curve-double-slit, non-parallel-curve-double slit experiments. The comprehensive-double-slit and irregular-double-slit experiments provide the new phenomena for developing theoretical model to study: (1) the nature of the light; (2) the wave theories of the light; (3) the quantum theory of the light. A complete explanation should describe all of the comprehensive double slit and irregular-double slit experiments consistently, which is a challenge. For this purpose, we propose a Dirac-type equation to describe the Particle pattern, Transition pattern and interference pattern produced by photons in a double slit experiment.